Cyber security : endpoint defense - Dewey, Gary (Packt Publishing, 2018)
"Computer and network security is very important and relevant in today's business world. Many system administrators and information technology professionals do not have formal training in computer security and may lack the budget to hire security professionals. They need an affordable solution to help them secure their data and improve their security posture. This video course will enable you to close the gap and be well acquainted with basic security fundamentals to improve their security. You will learn how to secure infrastructure, such as wireless access points, firewalls, and servers. Moving ahead, learn to secure applications and data by vulnerability scanning and patching, encryption, data loss prevention, and backups. Finally you will learn how to protect users from malware, phishing, and social engineering attacks and disaster recovery. By the end of the course, you will be a cyber security specialist capable of preventing data breaches and data loss, as these measures could save a company thousands of dollars. These topics are relevant to today's Information Technology environment and protection is vital to business success."--Resource description page